Double perovskite material and preparation method and application thereof

By doping rare earth element Er and transition metal Bi in the biperovskite material to form a material of Cs2AErZBi1-ZX6, the problem of the small luminescence wavelength range of the existing biperovskite material is solved, the luminescence wavelength is expanded to 1542nm, and the luminescence efficiency is improved. It is suitable for applications of a variety of optoelectronic devices.

CN119529835AActive Publication Date: 2025-02-28SHENZHEN TECH UNIV

Patent Information

Application Number
CN202411424414.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-28
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing dual perovskite materials have a small luminescence wavelength range, which is difficult to meet the needs of chip integration technology.

Method used

In the chemical formula of the biperovskite material of Cs2AErZBi1-ZX6, A is one of Ag, Na, and K, X is a halogen anion, and the rare earth element Er with 0 < Z < 1 is doped with the transition metal Bi to form a material with a 1542nm luminescence peak.

Benefits of technology

The light emission wavelength of the biperovskite material has been expanded to 1542nm, which enhances the luminous efficiency and is suitable for the applications of photodetectors, photovoltaic cells and light emitting diodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529835A_ABST
    Figure CN119529835A_ABST
Patent Text Reader

Abstract

The invention discloses a double perovskite material and a preparation method and application thereof, the chemical formula of the double perovskite material is Cs2AErZBi1-ZX6, A is one of Ag, Na and K, X is one or two of halogen anions, and Z is more than 0 and less than 1. According to the double-perovskite material provided by the invention, monovalent A (one of Ag, Na and K) ions and trivalent Er and Bi ions are used for replacing divalent Pb ions in a conventional double-perovskite material, so that the toxicity of the double-perovskite material is greatly reduced, and regulation and control of a perovskite band gap are realized to obtain the optical characteristic of a near-infrared II region. The rare earth element Er regulates and controls the energy level of the transition metal element Bi, so that the double perovskite material can realize a luminescence peak with the luminescence center of 1542nm. A detector prepared from the double perovskite material provided by the invention can realize visible-near infrared band (447-1550 nm) detection, I light / I dark in a visible light region can reach 104, and particularly, I light / I dark in 1550 nm and 1310 nm is greater than 102.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of near-infrared optoelectronic technology, and in particular to a double perovskite material and a preparation method and application thereof. Background Art

[0002] Near-infrared light is an electromagnetic wave with a wavelength in the range of 780-2526nm. It can be divided into short-wave near-infrared (780-1100nm) and long-wave near-infrared (1100-2526nm) with a wavelength of 1100nm as the boundary. Near-infrared light has been widely used in the fields of medicine, detection and communication due to its high temporal and spatial resolution and deep tissue penetration. Perovskite materials (APbX3) have high symmetry of three-dimensional crystals and Pb 2+ The unique electronic structure makes it one of the most promising candidate materials for high-quality light sources and high-definition displays in the future. However, due to the presence of Pb 2+ , so it has certain toxicity. In addition, due to the A in this material + Cations are usually organic ions or organic-inorganic hybrid ions, so they are easily decomposed when encountering water and oxygen in the air. Therefore, they have disadvantages such as poor stability in air and low device life.

[0003] To reduce the Pb content in perovskite materials 2+ To reduce the toxicity of Pb in APbX3 materials, researchers used a different-valent substitution method to replace 2+ Replaced with non-toxic or low-toxic trivalent transition metal or rare earth metal ions to form bimetallic double perovskite (A2B + B 3+ X6, typical A is Cs + , B + Ag + 、Na + , K + , Li + etc.; B 3+ for Bi 3+ , Sb 3+ 、In 3+ etc.; X is a halogen anion). Among them, A2B + B 3+ X6 is a three-dimensional bimetallic double perovskite material formed by replacing two lead ions with a monovalent and a trivalent cation. It has a variable chemical composition, which makes this type of material exhibit the advantages of long carrier lifetime, adjustable band gap, simple preparation method and good stability. It has broad application prospects in photovoltaic cells, light-emitting diodes (LEDs), photodetectors and other fields.

[0004] However, the luminescence wavelength of bimetallic double perovskite materials without ion doping is mainly concentrated in the visible light band. Double perovskite materials with emission wavelengths greater than 1000nm in the near-infrared band are relatively scarce, and there are problems such as low luminescence efficiency and difficulty in preparing into thin films, making it difficult to adapt to the needs of chip integration technology.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a double perovskite material and a preparation method and application thereof, aiming to solve the problem that the existing double perovskite material has a small luminescent wavelength range.

[0007] The technical solution of the present invention is as follows:

[0008] In a first aspect of the present invention, a double perovskite material is provided, wherein the chemical formula of the double perovskite material is Cs2AEr Z Bi 1-Z X6, wherein A is one of Ag, Na, and K, X is one or two of halogen anions, and 0<Z<1.

[0009] Preferably, the chemical formula of the double perovskite material is Cs2NaEr Z Bi 1-Z I 6-y Cl y ,Cs3Er Z Bi 1-Z I 6-y Cl y 、Cs2NaEr Z Bi 1-Z I6 or Cs2NaEr Z Bi 1-Z Cl6, wherein 0<y<6. For example, the chemical formula of the double perovskite material may be Cs2NaEr 0.05 Bi 0.95 Cl6、Cs2NaEr 0.05 Bi 0.95 I 5.5 Cl 0.5 、Cs2NaEr 0.05 Bi 0.95 I6, etc., but not limited to these.

[0010] A second aspect of the present invention provides a method for preparing the above-mentioned double perovskite material, the preparation method comprising the following steps:

[0011] Dissolving CsX, AX, ErX3 and BiX3 in a hydrohalic acid solution to form a double perovskite precursor solution;

[0012] The double perovskite precursor solution is subjected to a hydrothermal reaction to obtain a product having a chemical formula of Cs2AEr Z Bi 1-Z X6's double perovskite material.

[0013] Preferably, the molar ratio of CsX, AX, ErX3 and BiX3 is 2:1:Z:(1-Z).

[0014] Preferably, the temperature of the hydrothermal reaction is 150-180° C., and the time is 4-12 hours.

[0015] Preferably, after the double perovskite precursor solution undergoes a hydrothermal reaction, a double perovskite solution is obtained, and then the double perovskite solution is sequentially subjected to a cooling treatment, a washing treatment, and a drying treatment.

[0016] Preferably, the cooling treatment specifically comprises: cooling the double perovskite solution to room temperature.

[0017] Preferably, the washing treatment specifically comprises: filtering out the double perovskite powder from the double perovskite solution, and washing the double perovskite powder with one of anhydrous ethanol, methanol and isopropanol.

[0018] Preferably, the drying treatment is specifically: drying the washed double perovskite powder at a temperature of 60 to 100° C. for 4 to 12 hours.

[0019] The fourth aspect of the present invention provides the use of the above double perovskite material in photodetectors, photovoltaic cells and light-emitting diodes.

[0020] Beneficial effects: The present invention provides a double perovskite material and a preparation method and application thereof. The double perovskite material provided by the present invention replaces the divalent Pb ions in the conventional double perovskite with monovalent A (one of Ag, Na, K) ions and trivalent Er and Bi ions, thereby greatly reducing its toxicity. In addition, due to the regulation of the energy level of the transition metal element Bi by the rare earth element Er, the double perovskite material of the present invention can achieve a luminescence peak with a luminescence center of 1542nm.

[0021] The detector prepared by the double perovskite material provided by the present invention can realize the detection of the visible-near infrared band (447-1550nm), wherein the visible light region I 光 / I 暗 Up to 10 4 , especially, 1550nm and 1310nm I 光 / I 暗 Greater than 10 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1Cs2NaEr prepared in Example 1 of the present invention 0.05 Bi 0.95 X-ray diffraction pattern (a) and SEM pattern (b) of Cl6 double perovskite material and Cs2NaEr prepared in Example 2 0.05 Bi 0.95 I 5.5 Cl 0.5 X-ray diffraction pattern (c) and SEM image (d) of double perovskite material.

[0023] Figure 2 Cs2NaEr prepared in Example 1 of the present invention 0.05 Bi 0.95 UV-visible-near-infrared absorption graph (a) and Tauc plot (b) of Cl6 double perovskite material.

[0024] Figure 3 Cs2NaEr prepared in Example 1 of the present invention 0.05 Bi 0.95 Emission spectra of Cl6 double perovskite material under 980nm laser excitation: (a) 400-900nm, (b) 900-1700nm.

[0025] Figure 4 Cs2NaEr prepared in Example 2 of the present invention 0.05 Bi 0.95 I 5.5 Cl 0.5 (a) Absorption spectrum and photoluminescence spectrum, (b) Tauc plot of double perovskite materials.

[0026] Figure 5 IV curve diagram of the visible-near-infrared double perovskite detector prepared in the application example of the present invention under 19.8 mW optical power conditions and illumination at wavelengths of 447 nm, 520 nm, 669 nm, 808 nm, 1060 nm, 1310 nm, and 1550 nm. DETAILED DESCRIPTION

[0027] The present invention provides a double perovskite material and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0028] The embodiment of the present invention provides a double perovskite material, the chemical formula of the double perovskite material is Cs2AEr Z Bi 1- Z X6, wherein A is one of Ag, Na, and K, X is one or two of halogen anions, and 0<Z<1.

[0029] In some embodiments, the chemical formula of the double perovskite material is Cs2NaEr Z Bi 1-Z I 6-y Cl y ,Cs3Er Z Bi 1-Z I 6-y Cl y 、Cs2NaEr Z Bi 1-Z I6 or Cs2NaEr Z Bi 1-Z Cl6, where 0<y<6.

[0030] In this embodiment, Cs2NaEr x Bi 1-x I 6-y Cl y Take the example to explain the technical principle, and the same is true for other chemical formulas. x Bi 1-x I 6-y Cl y It is a co-doped compound based on the transition metal element Bi with a special electronic structure and the rare earth element Er with a relatively complex atomic structure. The Bi ion has multiple valence states of 0, +1, +2, +3 and +5, and has a strong spin-orbit coupling effect; the Er element 4 I 13 / 2 → 4 I 15 / 2 Fluorescence at about 1550nm can be obtained. 3+ The alloying effect makes Er 3+ The spacing between them increases, and the resulting lattice distortion promotes the Bi 3+ Xiang Er 3+ energy transfer, and finally achieve up-conversion ( 2 H 11 / 2 , 4 S 3 / 2 and 4 F 9 / 2 ) and down-conversion near infrared ( 4 I 13 / 2 → 4 I 15 / 2 ) is enhanced. In addition, Bi 3+ With Er 3+ The cross-relaxation between energy levels can make the Cs2NaEr provided in this embodiment x Bi 1-x I 6-y Cl yLuminescence and detection performance are achieved in the visible-near infrared II region (447-1550nm).

[0031] The embodiment of the present invention provides a method for preparing the above double perovskite material, and the preparation method comprises the following steps:

[0032] Dissolving CsX, AX, ErX3 and BiX3 in a hydrohalic acid solution to form a double perovskite precursor solution;

[0033] The double perovskite precursor solution is subjected to a hydrothermal reaction to obtain a product having a chemical formula of Cs2AEr Z Bi 1-Z X6's double perovskite material.

[0034] The preparation method provided in this embodiment combines solvent heat with vacuum evaporation to prepare Cs2AEr at a temperature not exceeding 160°C. Z Bi 1-Z X6's double perovskite material overcomes the shortcomings of high energy consumption in the traditional high-temperature calcination method to prepare near-infrared fluorescent materials.

[0035] In some embodiments, the molar ratio of CsX, AX, ErX3 and BiX3 is 2:1:Z:(1-Z).

[0036] In some embodiments, the hydrohalic acid solution is at least one of hydrochloric acid, hydroiodic acid, and hydrobromic acid.

[0037] In some embodiments, the hydrothermal reaction is carried out at a temperature of 150 to 180° C. and for a time of 4 to 12 hours.

[0038] If the temperature of the hydrothermal reaction is low, the solution cannot be completely dissolved, and there will be too many impurities during precipitation; if the temperature is too high, dangerous accidents are likely to occur, and the co-precipitation components may be uneven.

[0039] In some preferred embodiments, the temperature of the hydrothermal reaction is 160° C. and the time is 8 hours.

[0040] In some embodiments, after the double perovskite precursor solution undergoes a hydrothermal reaction, a double perovskite solution is obtained, and then the double perovskite solution is sequentially subjected to cooling treatment, washing treatment, and drying treatment.

[0041] In some embodiments, the cooling process is specifically: cooling the double perovskite solution to room temperature.

[0042] In some embodiments, the washing treatment specifically includes: filtering out the double perovskite powder from the double perovskite solution, and washing the double perovskite powder with one of anhydrous ethanol, methanol, and isopropanol.

[0043] In some embodiments, the drying process is specifically: drying the washed double perovskite powder at a temperature of 60 to 100° C. for 4 to 12 hours.

[0044] If the temperature is too low, it will be difficult to dry; if the temperature is too high, it will easily cause boiling and powder splashing.

[0045] In some preferred embodiments, the drying treatment is specifically: drying the washed double perovskite powder at a temperature of 80° C. for 8 hours.

[0046] In some embodiments, a method for preparing the above double perovskite material is provided, the preparation method comprising the following steps:

[0047] In a hydrothermal reactor at 160 °C, CsX, AX, ErX3 and BiX3 were dissolved in a hydrochloric acid solution at a molar ratio of 2:1:Z:(1-Z) to form a double perovskite precursor solution;

[0048] The double perovskite precursor solution is reacted at a temperature of 160° C. for 8 hours to obtain a double perovskite solution;

[0049] The double perovskite solution was cooled to room temperature, and the double perovskite powder was filtered out from the cooled double perovskite solution, and the double perovskite powder was washed three times with anhydrous ethanol, and then the washed double perovskite powder was dried at 80° C. for 8 h to obtain a double perovskite powder with a chemical formula of Cs2AEr Z Bi 1-Z X6's double perovskite material.

[0050] The embodiments of the present invention also provide applications of the double perovskite material in photodetectors, photovoltaic cells and light-emitting diodes.

[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are only for illustrating the present invention but not limiting the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0052] Example 1

[0053] Cs2NaEr 0.05 Bi 0.95 The preparation of Cl6 double perovskite material comprises the following steps:

[0054] a) 0.6734 g of cesium chloride, 0.1169 g of sodium chloride, 0.3648 g of erbium chloride, and 0.2102 g of bismuth chloride were added to a hydrothermal kettle in sequence, and then 25 mL of hydrochloric acid was added to the hydrothermal kettle. The hydrothermal kettle was sealed and heated in a 160° C. forced drying oven for 8 h;

[0055] b) Cool the sealed hydrothermal autoclave heated in step a) to room temperature with an ice-water bath, filter out the perovskite powder, wash it three times with anhydrous ethanol, filter out the perovskite powder and dry it in a drying oven at 80° C. for 8 h, then take it out and store it in a nitrogen glove box.

[0056] Example 2

[0057] Cs2NaEr 0.05 Bi 0.95 I 5.5 Cl 0.5 The preparation of double perovskite material comprises the following steps:

[0058] a) 1.0392 g of cesium iodide, 0.1169 g of sodium chloride, 0.3648 g of erbium chloride, and 0.2102 g of bismuth chloride were added to a hydrothermal kettle in sequence, and then 25 mL of hydrochloric acid was added to the hydrothermal kettle. The hydrothermal kettle was sealed and heated in a 160° C. forced air drying oven for 8 h;

[0059] b) Cool the sealed hydrothermal autoclave heated in step a) to room temperature with an ice-water bath, filter out the perovskite powder, wash it three times with anhydrous ethanol, filter out the perovskite powder and dry it in a drying oven at 80° C. for 8 h, then take it out and store it in a nitrogen glove box.

[0060] Example 3

[0061] Cs2NaEr 0.05 Bi 0.95 The preparation of I6 double perovskite material includes the following steps:

[0062] a) 1.0392 g of cesium iodide, 0.2998 g of sodium iodide, 0.7306 g of erbium iodide, and 0.3931 g of bismuth iodide were added to a hydrothermal kettle in sequence, and then 25 mL of hydrochloric acid was added to the hydrothermal kettle. The hydrothermal kettle was sealed and heated in a 160° C. forced air drying oven for 8 h;

[0063] b) Cool the sealed hydrothermal autoclave heated in step a) to room temperature with an ice-water bath, filter out the perovskite powder, wash it three times with anhydrous ethanol, filter out the perovskite powder and dry it in a drying oven at 80° C. for 8 h, then take it out and store it in a nitrogen glove box.

[0064] Comparative Example 1

[0065] Cs2NaBiI 5.5 Cl 0.5 The preparation of double perovskite material comprises the following steps:

[0066] a) 1.0392 g of cesium iodide, 0.1169 g of sodium chloride, and 0.6307 g of bismuth chloride were added to a hydrothermal kettle in sequence, and then 25 mL of hydrochloric acid was added to the hydrothermal kettle. The hydrothermal kettle was sealed and heated in a 160° C. forced air drying oven for 8 h;

[0067] b) Cool the sealed hydrothermal autoclave heated in step a) to room temperature with an ice-water bath, filter out the perovskite powder, wash it three times with anhydrous ethanol, filter out the perovskite powder and dry it in a drying oven at 80° C. for 8 h, then take it out and store it in a nitrogen glove box.

[0068] Comparative Example 2

[0069] Cc 0.05 Bi 0.95 I 5.5 Cl 0.5 The preparation of double perovskite material comprises the following steps:

[0070] a) 1.0392 g of cesium iodide, 0.2245 g of cesium chloride, 0.3648 g of erbium chloride, and 0.2102 g of bismuth chloride were added to a hydrothermal kettle in sequence, and then 25 mL of hydrochloric acid was added to the hydrothermal kettle. The hydrothermal kettle was sealed and heated in a 160° C. forced air drying oven for 8 h;

[0071] b) Cool the sealed hydrothermal autoclave heated in step a) to room temperature with an ice-water bath, filter out the perovskite powder, wash it three times with anhydrous ethanol, filter out the perovskite powder and dry it in a drying oven at 80° C. for 8 h, then take it out and store it in a nitrogen glove box.

[0072] Application Examples

[0073] A preparation method of a visible-near infrared double perovskite detector comprises the following steps:

[0074] (i) Substrate cleaning: The ITO glass substrate was ultrasonically cleaned in deionized water, isopropanol, acetone and ethanol for 20 min in sequence to remove surface stains, and then the organic solvent on the surface was removed using a nitrogen gun. It was then treated under ozone conditions for 20 min to remove residual organic reagents and improve the hydrophilic and hydrophobic properties of the substrate surface.

[0075] (ii) Preparation of electron transport layer: 50 mg / mL 15% MgO ZnO nano-ethanol solution was prepared with anhydrous ethanol to 20 mg / mL and vibrated in an ultrasonic cleaner for 5 min. 100 uL of the prepared nano-ZnO ethanol solution was drawn with a pipette and spin-coated at 2000 rpm for 30 s, followed by annealing at 100 °C for 15 min.

[0076] (iii) Preparation of double perovskite film: Cs2NaEr prepared in Example 1 0.05Bi 0.95 The Cl6 double perovskite material was placed in a thermal evaporation tungsten boat in a vacuum coating machine at a vacuum degree of 5×10 -4 Pa, 35W power, at a deposition rate of 0.2 angstroms (0.1 nm) / s, Cs2NaEr 0.05 Bi 0.95 The Cl6 double perovskite material was evaporated onto the ITO glass substrate with spin-coated ZnO to form a polycrystalline film. The evaporated sample was taken out from the vacuum coating machine and placed on a 160°C heating table for annealing at 160°C for 15 minutes to promote the densification of the polycrystalline film and reduce film defects.

[0077] (iv) Preparation of hole transport layer and silver electrode: 12 mg of poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4-(N-(4-sec-butylphenyl)diphenylamine)] (TFB) was added to a glass bottle containing 1 mL of chloroform and shaken to dissolve. 90 uL of TFB solution was spin-coated at 3000 rpm for 30 s. The spin-coated device was transferred to a vacuum coating machine and heated at a vacuum degree of 5 × 10 -4 Pa, 42W power conditions, 10nm MoO3 hole transport layer was evaporated at a deposition rate of 0.1 angstrom (0.1nm) / s; under a vacuum degree of 5×10 -4 Under the conditions of 82W power, 20nm of Ag was evaporated at a deposition rate of 0.5Å (0.1nm) / s, and then the Ag electrode thickness was evaporated to 100nm at a deposition rate of 1.0Å (0.1nm) / s.

[0078] Performance testing

[0079] 1. Cs2NaEr prepared in Example 1 0.05 Bi 0.95 Cl6 double perovskite material and Cs2NaEr prepared in Example 2 0.05 Bi 0.95 I 5.5 Cl 0.5 Double perovskite materials were characterized by X-ray diffraction and SEM, such as Figure 1 .

[0080] Figure 1 (a) is Cs2NaEr prepared in Example 1 of the present invention 0.05 Bi 0.95 X-ray diffraction patterns of Cl6 double perovskite materials and Cs2NaBiCl6 (ICSD No. 77-1831) and Cs2NaErCl6 (ICSD No. 890053) standard samples. It can be seen from the figure that the strong diffraction peaks at the central diffraction peaks at 14.18°, 28.52° and 59.00° are Cs2NaEr 0.05 Bi0.95 The diffraction peaks of the (111), (222) and (444) planes of the Cl6 double perovskite material correspond to the Fm3m space group. The central peak position of its diffraction peak is significantly offset from the diffraction peaks of the (111), (222) and (444) planes of the Cs2NaBiCl6 and Cs2NaErCl6 standard samples. This is because the alloying of the transition metal element Bi and the rare earth element Er causes the lattice to change, making the Cs2NaEr 0.05 Bi 0.95 The diffraction peak position of the (111) plane of the Cl6 double perovskite material shifts from the low angle of Cs2NaBiCl6 to the large angle of Cs2NaErCl6. Figure 1 (b) is Cs2NaEr prepared in Example 1 of the present invention 0.05 Bi 0.95 Scanning electron microscope (SEM) image of Cl6 double perovskite material annealed at 160℃ for 5min. 0.05 Bi 0.95 Cl6 double perovskite is polycrystalline, and the average size of a single grain is 200-500nm. Figures (c) and (d) are Cs2NaEr prepared in Example 2 of the present invention. 0.05 Bi 0.95 I 5.5 Cl 0.5 XRD and SEM images of double perovskite materials.

[0081] 2. Cs2NaEr prepared in Example 1 0.05 Bi 0.95 Cl6 double perovskite materials were subjected to UV-visible-near infrared absorption and band gap detection, such as Figure 2 .

[0082] Figure 2 (a) is Cs2NaEr prepared in Example 1 of the present invention 0.05 Bi 0.95 UV-visible-near infrared absorption curve of Cl6 double perovskite material. 0.05 Bi 0.95 The Cl6 double perovskite material has a strong absorption peak at around 375nm, and weaker absorption states exist at 530nm, 750nm, and 1200nm. 0.05 Bi 0.95 The band gap of Cl6 double perovskite materials was determined (see Figure 2 (b)). Linear fitting of the absorption edge gives a photon energy of 3.10 eV, i.e., Cs2NaEr 0.05 Bi 0.95 The band gap size of Cl6 double perovskite material is 3.10eV.

[0083] 3. Cs2NaEr prepared in Example 1 0.05 Bi 0.95 Cl6 double perovskite material is excited by 980nm laser, such as Figure 3 .

[0084] from Figure 3 It can be seen that the Cs2NaEr 0.05 Bi 0.95 Under 980nm laser excitation, the Cl6 double perovskite material exhibits upconversion ( Figure 3 (a)) and down conversion ( Figure 3 (b) phenomenon. This is due to Er 3+ The doping of Bi 3+ The spacing between them increases, and the resulting lattice distortion promotes the Bi 3+ Xiang Er 3+ energy transfer, ultimately leading to upconversion to 535nm ( 2 H 11 / 2 ), 558nm( 4 S 3 / 2 ) and 663nm( 4 F 9 / 2 )arrive 4 I 15 / 2 The transition and down conversion of 1542nm ( 4 I 13 / 2 → 4 I 15 / 2 ) enhancement.

[0085] 4. Cs2NaEr prepared in Example 2 0.05 Bi 0.95 I 5.5 Cl 0.5 Double perovskite materials were tested for UV-visible absorption and photoluminescence, such as Figure 4 .

[0086] Figure 4 (a) is Cs2NaEr prepared in Example 2 of the present invention 0.05 Bi 0.95 I 5.5 Cl 0.5 UV-visible absorption curve and PL curve of double perovskite materials. As can be seen from the figure, Cs2NaEr 0.05 Bi 0.95 I 5.5 Cl 0.5 Double perovskite materials have a strong absorption peak at around 650nm and an absorption tail at 700-800nm. 0.05 Bi 0.95 I5.5 Cl 0.5 The band gap of double perovskite materials was determined (see Figure 4 (b)). Linear fitting of the absorption edge yields photon energies of 1.59 eV and 1.89 eV, respectively. The average of the two gives Cs2NaEr 0.05 Bi 0.95 I 5.5 Cl 0.5 The band gap size of double perovskite material is 1.74eV.

[0087] 5. Figure 5 The IV curves of the visible-near-infrared double perovskite detector prepared for the application example under 19.8mW optical power at 447nm, 520nm, 669nm, 808nm, 1060nm, 1310nm, and 1550nm wavelengths. The detector exhibits an ultra-wide spectral response in the visible-near-infrared region, where the I 光 / I 暗 Greater than 10 4 , and the 1550nm and 1310nm I 光 / I 暗 Greater than 10 2 .

[0088] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A double perovskite material, characterized in that: The chemical formula of the double perovskite material is Cs2AEr Z Bi 1-Z X6, wherein A is one of Ag, Na, and K, X is one or two of halogen anions, and 0<Z<1.

2. The double perovskite material according to claim 1, characterized in that: The chemical formula of the double perovskite material is Cs2NaEr Z Bi 1-Z I 6-y Cl y ,Cs3Er Z Bi 1-Z I 6-y Cl y 、Cs2NaEr Z Bi 1-Z I6 or Cs2NaEr Z Bi 1-Z Cl6, where 0<y<6.

3. A method for preparing the double perovskite material according to claim 1, characterized in that: The preparation method comprises the following steps: Dissolving CsX, AX, ErX3 and BiX3 in a hydrohalic acid solution to form a double perovskite precursor solution; The double perovskite precursor solution is subjected to a hydrothermal reaction to obtain a product having a chemical formula of Cs2AEr Z Bi 1-Z X6's double perovskite material.

4. The method for preparing a double perovskite material according to claim 3, characterized in that: The molar ratio of CsX, AX, ErX3 and BiX3 is 2:1:Z:(1-Z).

5. The method for preparing double perovskite material according to claim 3, characterized in that: The temperature of the hydrothermal reaction is 150-180° C. and the time is 4-12 hours.

6. The method for preparing a double perovskite material according to claim 3, characterized in that: After the double perovskite precursor solution undergoes a hydrothermal reaction, a double perovskite solution is obtained, and then the double perovskite solution is subjected to a cooling treatment, a washing treatment, and a drying treatment in sequence.

7. The method for preparing a double perovskite material according to claim 6, characterized in that: The cooling treatment specifically includes: cooling the double perovskite solution to room temperature.

8. The method for preparing a double perovskite material according to claim 6, characterized in that: The washing treatment specifically includes: filtering out the double perovskite powder from the double perovskite solution, and washing the double perovskite powder with one of anhydrous ethanol, methanol and isopropanol.

9. The method for preparing a double perovskite material according to claim 6, characterized in that: The drying treatment specifically includes drying the washed double perovskite powder at a temperature of 60 to 100° C. for 4 to 12 hours.

10. Use of the double perovskite material according to claim 1 in photodetectors, photovoltaic cells and light-emitting diodes.

Citation Information

Patent Citations

  • Near ultraviolet excited double perovskite single matrix white light fluorescent material and preparation and application thereof

    CN108659827A

  • Yb &lt; 3 + &gt; / Er &lt; 3 + &gt; doped Cs2NaBiCl6 up-conversion luminescence temperature sensing fluorescent material and preparation method thereof

    CN116656357A

Cited By

  • A first main group metal gradient-doped Cs2NaBiCl6 perovskite material, a preparation method and application thereof

    CN122625239A